2012
DOI: 10.1113/jphysiol.2011.226555
|View full text |Cite
|
Sign up to set email alerts
|

Human responses to bright light of different durations

Abstract: Key points• Light is the strongest time cue for entrainment and phase resetting of the circadian clock.• In humans, exposure to long-duration light (6.5 h) in the late evening/early night causes phase delays, suppresses melatonin and increases alertness.• Here we studied the effects of different durations of exposure to a single high-intensity (∼10,000 lux) light pulse (0.2 h, 1 h, 2.5 h and 4.0 h) on phase shifting, suppression of melatonin and self-reported sleepiness in young men and women.• Phase-resetting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
201
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(225 citation statements)
references
References 41 publications
15
201
2
2
Order By: Relevance
“…We could have, as many laboratories do, used an antimuscarinic agent to dilate the pupils to avoid the pupillary light reflex and keep it from interfering with the amount of light striking the retina. Given the potential effect of antimuscarinics on the physiologic properties of retinal ganglion cells (74), we feel that the use of such agents would have created greater uncertainty in the interpretation of our results.A final consideration is that the phase shift observed in our study under continuous light was smaller than that observed in previous studies (41,49). This difference, however, is likely due to protocol dissimilarities in the intensity of the light exposure (49) and light history of the participants that could lead to a different sensitization of the photoreceptive system (41).…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…We could have, as many laboratories do, used an antimuscarinic agent to dilate the pupils to avoid the pupillary light reflex and keep it from interfering with the amount of light striking the retina. Given the potential effect of antimuscarinics on the physiologic properties of retinal ganglion cells (74), we feel that the use of such agents would have created greater uncertainty in the interpretation of our results.A final consideration is that the phase shift observed in our study under continuous light was smaller than that observed in previous studies (41,49). This difference, however, is likely due to protocol dissimilarities in the intensity of the light exposure (49) and light history of the participants that could lead to a different sensitization of the photoreceptive system (41).…”
contrasting
confidence: 51%
“…of NIF photoreception in humans remains incompletely understood, as it has wavelength (35)(36)(37)(38)(39), intensity (40), duration (41), and pattern (42)(43)(44) responses that are considerably distinct from the traditional perceptual image-forming responses, and most knowledge in this field has been imputed from studies of nonhuman mammals. Understanding NIF characteristics and responses to light is crucial for the development and optimization of light therapy strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The current study confirms the results of the controlled lab studies [16,35] and supports the conclusion that a combination of short light pulses of 30 min. in the morning and dim light in the evening is also capable of advancing the melatonin rhythm when applied in a home situation with no real control over environmental light.…”
Section: Discussionsupporting
confidence: 81%
“…The 1h light pulses in the study of St. Hilaire et al [16] in humans elicited a maximal phase advance of 1.2h, which is 44% of the response of 2.7h generated by the 6.7h light exposure in the study of Khalsa et al [13]. Such dimin.ishing responses to extended stimulation are considered the result of adaptation processes; therefore the beginning of a light pulse is most important for the phase shifting effects [17].…”
Section: Introductionmentioning
confidence: 99%
“…Changing the sleep-wake cycle and ALAN resulted in phase advance of the MLT rhythm, which also reduced the circadian amplitude of the hormone in healthy men [222]. MLT suppression by ALAN has a dose-dependent response to both irradiance level and duration of the exposure [223]. Furthermore, the phase advance and suppression in MLT rhythms are intimately wavelength-dependent with more manifested effect at short wavelengths compared with long wavelengths [44,45,224].…”
Section: Circadian Disruption Biomarkers In Obesity and Cancer Researchmentioning
confidence: 92%